Similar Yield Benefits of Hybrid, Conventional, and Organic Tomato and Sweet Pepper Varieties Under Well-Watered and Drought-Stressed Conditions - Ficiciyan, Anoush Miriam; Loos, Jacqueline; Tscharntke, Teja (Frontiers in Sustainable Food Systems, 2021)
Global agrobiodiversity is threatened by the replacement of traditional, locally adapted crop varieties with high-yielding and hybrid varieties during the past 60 years, resulting in associated losses of crop, variety, and allele diversity. Locally adapted, traditional varieties are known to perform equal or even better under environmental stress conditions and to be more resilient in unstable cultivation environments. Therefore, European organic vegetable breeding organizations conserve local, traditional varieties and breed new varieties in low-input organic environments, aiming to increase the range of varieties for sustainable cultivation under sub-optimal growing conditions. However, performance of organic vegetable varieties, in comparison to conventional high-yielding and hybrid varieties, under different environmental conditions has not been intensively researched. To contribute to this scientific field, we compared the agronomic and quality performance between hybrid, conventional, and organic tomato and sweet pepper varieties, two economically important species on the EU market under a) well-watered and b) drought stress conditions, using five different varieties (i.e. 30 varieties) as replicates in each of the six groups. Performance of both species was negatively affected by drought, regardless of the breeding background. Equally, for tomato and sweet pepper, hybrids produced higher amounts of individual fruits, however total yield in kg was comparable for hybrid, conventional and organic plants. Considering the agro-ecological importance of enlarging and securing variety diversity in light of changing environmental conditions, we show that the assumed benefits of the hybrids can also be delivered by the organic and conventional varieties. These varieties should be considered as an important source of genetic resources, supporting farmers to adapt to their local climate and environmental conditions in the future.